532. Recurrent C. difficile in Children: Not Easy to Cure. (26th November 2018) - Lee, Philip; Aroniadis, Olga; Noble, Sarah; Rimawi, Fatimah; Goldman, David
Abstract: Background: Little is known about the clinical characteristics and appropriate treatment of children with repeated C. difficile infections (rCDI). Current IDSA treatment recommendations for rCDI include oral vancomycin (VAN) or metronidazole (MTZ) based on weak/low-quality evidence. Methods: We performed a retrospective chart review of children hospitalized at CHAM with rCDI from September 2009 to October 2017. This cohort was extracted using ICD 9 or 10 codes from the electronic health record. Subsequent full chart review was performed to identify patients with rCDI, which was defined as symptomatic diarrhea in the context of repeat positive C. difficile toxin assay and diarrhea. Recurrence (recr), relapse (rspd), and cure with relapse (CWR) were defined based on time to new CDI: >14–60, ≤365, and >365 days, respectively. Global cure (G/C) was defined as the absence of rCDI up to April 2018. Symptoms severity was graded based on the presence of WBC >12 or <2 k/μL, elevated creatinine adjusted by age, and serum albumin <3 mg/dL. Fisher's exact, χ 2, Mann–Whitney were used for analyses. Results: We identified 28 children with rCDI (12 males and 16 females) with an average age of 9 ± 6 years. The threemost common diseases associated with rCDI were ( n, %): stem cell transplantation (8, 28.6%), malignancy (6, 21.4%), and IBD (5, 17.9%). After the first episode of rCDI, 53.5% (95% CI 34–72%) experienced recr, rspd or CWR with an average number of 1.27 ± 0.46 repeat CDI episodes. The symptoms of rCDI were generally mild ( n = 24; 85.7%), while moderate ( n = 3; 10.7%), and severe disease ( n = 1; 3.6%) were significantly less common ( P = <0.001). Antibiotics used to treat first episode of rCDI are shown in Table 1. Average number of days from treatment of first to second rCDI did not significantly differ among treatment courses (MTZ: 123 days vs. VAN: 60 days; P = 0.91). The frequency of G/C increased with treatment course as follows: first (46.4%), second (60%) and third (83.3%) ( χ 2 for trend, P = 0.09, Table 1). Conclusion: Multiple rCDI occurred in a significant proportion of children with relatively poor clinical response. MTZ was disproportionately used in the treatment of rCDI. The use of NTZ appears to be associated high rate of G/C although our numbers were very small. Additional multi-site study is indicated to determine the optimal treatment of children with rCDI. Disclosures: P. Lee, Astra Zenena: Consultant, Consulting fee.